Aptamer functionalized multifunctional fluorescent nanotheranostic platform for pancreatic cancer - Nigam, Preeti; Waghmode, Shobha A.; Yeware, Amar M.; Nawale, Laxman U.; Dagde, Priyanka; Dudhane, Amol; Sarkar, Dhiman (Journal of Nanopharm Drug Delivery, 2014)
This study explores the potential of aptamer functionalized and fluorescent silver nanoparticles (AgNPs) labeled human serum albumin nanoparticles for drug delivery and bioimaging. Nanotechnology is certainly the most promising research arena in recent years and different fields of biotechnology, medicine and agricultural have been deeply benefited by the enormous advantages of nanotechnology. In recent years, synthesis of nanoparticles via eco-friendly methods has attained a lot of interest and silver nanoparticles are synthesized extensively due to their size tunable properties and vast applicability in different areas. In this study we have explored green synthesized fluorescent silver nanoparticles as a novel bioimaging agent for pancreatic cancer. Capsaicin, a plant phytochemical found in red chilli pepper was encapsulated in aptamer MUC-1 coupled albumin nanoparticles and it was observed that the nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in-vitro. Meanwhile AgNPs mediated excellent bioimaging has enhanced the efficacy of our system as drug delivery vehicle.

Antibacterial and anti-TB tat-peptidomimetics with improved efficacy and half-life - Bhosle, Govind S.; Nawale, Laxman; Yeware, Amar M.; Sarkar, Dhiman; Fernandes, Moneesha (European Journal of Medicinal Chemistry, 2018)
Non-natural antimicrobial peptides are ideal as next-generation antibiotics because of their ability to circumvent the problems of drug resistance and in vivo instability. We report novel all-alpha- and alpha,gamma-mixed Tat peptide analogues as potential antibacterial and anti-TB agents. These peptides have broad spectrum antibacterial activities against Gram-positive (MICs 0.61 +/- 0.03 to 1.35 +/- 0.21 mu M with the peptide gamma TatM4) and Gram-negative (MICs 0.71 +/- 0.005 to 1.26 +/- 0.02 M with gamma TatM4) bacteria and are also effective against active and dormant forms of Mycobacterium tuberculosis, including strains that are resistant to rifampicin and isoniazid. The introduction of the non-natural amino acids of the study in the Tat peptide analogues results in increased resistance to degradation by proteolysis, significantly increasing their half-life. The peptides appear to inhibit bacteria by a membrane disruption mechanism, and have only a low cytotoxic effect on mammalian cells. (C) 2018 Elsevier Masson SAS. All rights reserved.